Comparison of Mortality Rates between Italian and Foreign-born Patients with Alcohol Use Disorders. Issue 5 (20th October 2022) - Pavarin, Raimondo Maria; Fioritti, Angelo; Fabbri, Chiara; Sanchini, Samantha; De Ronchi, Diana
ABSTRACT: In Italy, although the number of foreign-born residents has grown exponentially, there are no data on mortality risk among migrants who have alcohol use disorders (AUDs). We examined the mortality risk and causes of death for natives and non-natives in a cohort of individuals treated for AUDs in Northern Italy in the period from 01/01/1975 to 31/12/2016. We highlight important characteristics of non-natives compared to Italians: 1) a younger age and a higher proportion of females; 2) a better health status; 3) a better social capital 4) a lower risk of death. We found differences in mortality between the various areas of origin, with a higher risk among participants born in Asia and African countries other than Mediterranean. The excess mortality compared to the reference population (SMRs) was at least three times for Italians and two times for migrants. While the non-native patients with AUDs have in general better health than Italians with AUDs, our results highlighted higher percentage of dropouts from treatment and lower access to Mental Health Services, suggesting that barriers to the access and completion of therapeutic programs still exist.